Where the Normal is Crisis: Service Delivery to Underserved Populations during the COVID Pandemic - Nourpanah, Shiva (Anthropologica)

(untitled) (University of Victoria, 2021)
Women and children subject to violence. Refugees. The incarcerated and criminalized. The homeless. Ethnic and racialized minorities. When a global pandemic hits populations that are already vulnerable, racialized, marginalized, historically subject to oppression, and underserved, the civil society organizations mandated to serve them need all their ingenuity and resourcefulness to provide support while following public health guidelines. As the COVID‑19 global pandemic forced the closure of many workplaces and the re-direction of public social life, the daily lives of vulnerable people, many already struggling on the margins of society, and those mandated to serve and support them changed shape drastically in some ways, and in other ways, not so much. My main argument is that the pandemic of 2020 and consequent imposed restrictions brought about a moment of difference in how our society treats those who are usually and in “normal” times pushed to the margins, invisible and overlooked. Policy spotlight, propelled by panic and a global public health crisis, shone on them, rendering them sharply visible.